Modelo de gestión financiera para mejorar la rentabilidad y liquidez de la granja avícola “Regalo de Dios” período 2019 - 2020. - Villacís Mora, Ximena Elizabeth (2021)
The objective of this research was to design a financial management model for the adequate management of economic resources in the Regalo de Dios Poultry Farm. For its accomplishment, a study was carried out with a mixed exploration approach, since qualitative instruments such as the observation and the interview tools were used, and quantitative instruments such as the questionnaire. Likewise, the data collected were analyzed by means of a descriptive level of study, in which the information obtained with the applied instrument is presented graphically. The results obtained with the financial analysis showed that there are low liquidity indexes, a decrease in profitability and high indebtedness indexes. In addition, the interviews revealed difficulties in financial management, problems in decision making and the lack of an optimal financial management model for the farm. To overcome the problems identified above, a model was proposed that introduces the methodology for calculating production costs, depreciation of fixed assets and recognition of biological assets, a methodology for recording costs that will allow control of resources and improve the profit margin. In the validation of the proposal made through the ARIMA time series forecasting model, it was possible to project a growth in sales for the period 2022 to 2024.